Clinical and laboratory aspects of the new coronavirus infection in newborns and infants - M. K. Ermakova; S. N. Najdyonkina; L. P. Matveeva (Детские инфекции (Москва))
Purpose: to identify clinical and laboratory aspects of a new coronavirus infection in newborns and infants. Materials and methods: a retrospective analysis of 131 observations of newborns and infants infected with SARS-CoV-2 treated in children's infectious diseases departments of Izhevsk was carried out. Results. The course of coronavirus infection in newborns and infants who became ill on an outpatient basis and were hospitalized did not have significant specific clinical and laboratory features and was similar to the symptoms of major respiratory infections. Among the hospitalized, 80.9% of children had a mild severity of coronavirus infection, the rest of the children had a moderate course. The clinical picture was dominated by cough (86.3%), nasal congestion (74%) and fever (71.8%). Significant clinical differences were obtained in newborns in the form of predominance of nasal obstruction, and in infants in the predominance of fever and dry cough. Pneumonia was diagnosed in 19.1% in the form of a mild, mainly bilateral lesion.